Marketing Strategy for Life Insurance Companies in Reaching the Millennial Generation - Lestari, Sri (Lafadz Jaya Publisher, 2023)
The current Covid-19 pandemic is a catalyst for social, economic, business and even consumer behavior change. These changes have forced the life insurance industry into a corner with the necessity to make changes on a large scale that may not have been imagined before. Millennials will be the target of all insurance companies, not only digital-based insurance companies, but other insurance companies that have just become aware of the swift technological disruption. In this case, insurance companies face the challenge of educating the millennial generation to become insurance buyers. This study uses the method of literature study. The results of this research are in the form of insurance marketing strategies for millennials including: 1) Explorative business and technology roadmap; 2) Expand digital scale to engage with the millennial generation; 3) Adopt a new method of distribution management; 4) Focus on consumer data governance and management.